A reduction in the knee adduction moment with medial thrust gait is associated with a medial shift in center of plantar pressure. Issue 7 (July 2016) - Ferrigno, Christopher; Wimmer, Markus A; Trombley, Robert M; Lundberg, Hannah J; Shakoor, Najia; Thorp, Laura E
Highlights: There is an association between shifts in plantar pressure and changes in knee loads. Medial foot center of pressure is associated with a reduced knee adduction moment. When the barefoot center of pressure lateralizes, the knee adduction moment increases. Abstract: The knee adduction moment (KAM) is an established marker of compartmental load distribution across the tibiofemoral joint. Research suggests a link between the magnitude of the KAM and center of plantar pressure (COP) thus alterations in the two may be related. The objective of this study was to investigate whether the COP predictably shifts when the KAM is reduced through a gait adaptation. Twenty healthy adults underwent gait analysis walking with their normal gait pattern and with medial thrust gait, a gait adaptation known to significantly reduce the KAM. Simultaneous COP and 3-D kinetics were acquired to allow for a comparison of the change in COP to the change in the KAM. The COP was quantified by determining a customized medial-lateral pressure index (MLPI) which compares the COP tracing line during the first and second halves of stance to the longitudinal axis of the foot. Linear regressions assessing the association between the changes in KAM and MLPI indicated that 48.3% ( p = 0.001) of the variation in MLPI during the first half of stance can be explained by the KAM during the same period. A trend was observed between the association between the KAM and MLPI during the second half of stance ( R 2 = 0.16, p = 0.080). Backwards elimination regression analysis was used to explore whether simultaneous consideration of the KAM and other potential confounding factors such as sagittal plane knee moments and speed explained variance in the MLPI during the first half of stance. Only the KAM exhibited explanatory power ( β = 0.695, p = 0.001). During medial thrust gait, a reduction in the KAM was associated with a medial shift in the MLPI, and an increase in the KAM was associated with a lateral shift in the MLPI, especially in the first half of the stance phase. Together, these results demonstrate an inherent link between foot pressure and the KAM during medial thrust gait, and suggest that manipulating foot pressure may be a biomechanical mechanism for an intervention designed to improve loading conditions at the knee.